2015
DOI: 10.1158/1535-7163.mct-15-0553
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of PARP Inhibitor Rucaparib in Orthotopic Glioblastoma Xenografts Is Limited by Ineffective Drug Penetration into the Central Nervous System

Abstract: Poly (ADP-ribose) polymerase (PARP) inhibition can enhance the efficacy of temozolomide (TMZ) and prolong survival in orthotopic glioblastoma (GBM) xenografts. The aim of this study was to evaluate the combination of the PARP inhibitor rucaparib with TMZ and to correlate pharmacokinetic and pharmacodynamic studies with efficacy in patient-derived GBM xenograft models. The combination of rucaparib with TMZ was highly effective in vitro in short-term explant cultures derived from GBM12, and similarly, the combin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 51 publications
(60 reference statements)
3
62
1
Order By: Relevance
“…The in vivo TAL dosing strategy and CNS distribution evaluation in this study were pertinent because the plasma concentration of TAL achieved two hours after drug administration was similar to that measured in the phase I clinical trial (67.1 nmol/L in mice vs. 50 nmol/L in human)(44). Comparing the pharmacokinetics of TAL to other PARP inhibitors, the brain-to-plasma concentration ratio for TAL (0.02) is lower than that of rucaparib (0.11), which also lacked efficacy in orthotopic glioma models(42). Alternatively, veliparib has a much higher brain-to-plasma concentration ratio (0.47) than either TAL or rucaparib despite the efflux liability of veliparib to MDR1 and BCRP (16, 45).…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo TAL dosing strategy and CNS distribution evaluation in this study were pertinent because the plasma concentration of TAL achieved two hours after drug administration was similar to that measured in the phase I clinical trial (67.1 nmol/L in mice vs. 50 nmol/L in human)(44). Comparing the pharmacokinetics of TAL to other PARP inhibitors, the brain-to-plasma concentration ratio for TAL (0.02) is lower than that of rucaparib (0.11), which also lacked efficacy in orthotopic glioma models(42). Alternatively, veliparib has a much higher brain-to-plasma concentration ratio (0.47) than either TAL or rucaparib despite the efflux liability of veliparib to MDR1 and BCRP (16, 45).…”
Section: Discussionmentioning
confidence: 99%
“…25 These studies apparently explained that the expression level of INPP4B was negatively correlated F I G U R E 5 Effect of rucaparib on cell proliferation and apoptosis in both SaOS2 and U2OS cells. 29,30 However, the effect of rucaparib on the treatment of OS has not been investigated. A, B, MTT assay results showed that rucaparib significantly reduced cell viability at a dose-dependent and time-dependent manners.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study reported that rucaparib had poor penetration into the CNS, suggesting it would have limited activity as a temozolomide sensitizer in GBM (15). Recently, however, the field has been revitalized by the demonstration that olaparib penetrates GBM at therapeutic levels in situ in patients (16), and also by promising toxicity and efficacy data arising from a phase I study of veliparib in combination with whole brain radiotherapy for brain metastases (17), and several phase I studies are now underway.…”
Section: Manuscriptmentioning
confidence: 99%